Optimal timetable development for community shuttle network with metro stations - Xiong, Jie; He, Zhengbing; Guan, Wei; Ran, Bin (Transportation research. Part C, Emerging technologies, 2015)
•Two constraints, i.e., vehicle loading and fleet size, are considered in the problem.•A timetable generating method under the fleet size constraint is proposed.•An algorithm, called FW-SDT, is proposed to solve the problem.•FW-SDT is suitable for any continuous passenger’s arrival distribution.•FW-SDT outperforms GA in both accuracy and effectiveness. This paper investigates an issue for optimizing synchronized timetable for community shuttles linked with metro service. Considering a passenger arrival distribution, the problem is formulated to optimize timetables for multiple community shuttle routes, with the objective of minimizing passenger’s schedule delay cost and transfer cost. Two constraints, i.e., vehicle capacity and fleet size, are modeled in this paper. The first constraint is treated as soft, and the latter one is handled by a proposed timetable generating method. Two algorithms are employed to solve the problem, i.e., a genetic algorithm (GA) and a Frank–Wolfe algorithm combined with a heuristic algorithm of shifting departure times (FW-SDT). FW-SDT is an algorithm specially designed for this problem. The simulated and real-life examples confirm the feasibility of the two algorithms, and demonstrate that FW-SDT outperforms GA in both accuracy and effectiveness.